Legal Policy for Community Welfare Based Mining Management - Warsito (MultiTech Publisher, 2023)
This paper focuses on community welfare-based mining management legal policies with the aim of improving the welfare of communities around the mine. The research method used is normative legal research with a statutory approach, case approach and conceptual approach. The results of the research show that the legal policy for managing metallic mineral mining in improving the welfare of communities around the mine is based on four main pillars, namely legal policy for democratic mineral and coal mining management, mineral and coal mining governance using good governance performance standards. Realizing social justice in the fifth principle of Pancasila, and monitoring and enforcing the law against perpetrators of environmental destruction and pollution in the mining sector. The concept of managing metal mineral (nickel) mining based on the welfare of communities around the mine involves regulations regarding licensing, land use, regional development, CSR programs, and participation of local communities in community development programs implemented by mining companies.